Analysis of an Extreme Scenario in the Vacuum Vessel in KTX. (June 2015) - Luo, Zhiren; Yang, Qingxi; Song, Yuntao; Li, Hong; Liu, Wandong; Du, Shuangsong; Xu, Hao; Wang, Zhongwei; Yao, Yao; Hu, Huan
Abstract The Vacuum Vessel (VV) system is a vital component of Keda Torus for eXperiment (KTX). Various accidental scenarios might occur on the VV. In this report, an extreme scenario is assumed and studied: plasma accidental termination during the flat-top stage. Numerical simulations based on finite element are performed as the major tool for analyses. The detailed distributions of eddy and the reaction forces on VV are extracted, and the total eddy current and the maximum reaction force due to electromagnetic load are figured out. In addition, according to the results, the VV can be approximately regarded as a centrally symmetric structure, even though its ports distribution is asymmetric.